The Role of Product Reviews as a Mediator of Influencer Marketing and Tiktok Visual Content on Purchase Decisions - Meylani, Safna Dwi; Ali, Ali (Islamic University of Kalimantan MAB Banjarmasin, 2026)
AbstractThis study examines the impact of influencer marketing and visual content on purchasing decisions for Skintific products on TikTok through product review mediation. The population of this study was Skintific product users residing in Jepara, Central Java, using quantitative methods and analyzed with PLS-SEM 4.0. The results show that influencer marketing, visual content, and product reviews have a significant positive effect on purchasing decisions. Product reviews are proven to mediate the relationship between influencer marketing and purchasing decisions, but visual content does not. These findings confirm the credibility of influencers in shaping consumer trust and psychological motivation compared to visual content. Based on the Stimulus Organism Response (SOR) theory, digital stimuli from social and visual content are effective in triggering emotional responses that drive consumer purchasing behavior.Keywords: Influencer Marketing; Visual Content; Product Reviews; Purchasing Decisions